Gut microbial assessment among Hylobatidae at the National Wildlife Rescue Centre, Peninsular, Malaysia - Roberta Chaya Tawie, Tingga; Millawati, Gani; Mohd Ridwan, Abd Rahman; Badrul Munir, Md Zain (The Korean Society of Veterinary Science, 2024)
Importance: Recent developments in genetic analytical techniques have enabled the comprehensive analysis of gastrointestinal symbiotic bacteria as a screening tool for animal health conditions, especially the endangered gibbons at the National Wildlife Rescue Centre (NWRC). Objective: High-throughput sequencing based on 16S ribosomal RNA genes was used to determine the baseline gut bacterial composition and identify potential pathogenic bacteria among three endangered gibbons housed in the NWRC. Methods: Feces were collected from 14 individuals (Hylobates lar, n = 9; Hylobates agilis, n = 4; and Symphalangus syndactylus, n = 1) from March to November 2022. Amplicon sequencing were conducted by targeting V3–V4 region. Results: The fecal microbial community of the study gibbons was dominated by Bacteroidetes and Firmicutes (phylum level), Prevotellaceae and Lachnospiraceae/ Muribaculaceae (family level), and Prevotella (and its subgroups) (genera level). This trend suggests that the microbial community composition of the study gibbons differed insignificantly from previously reported conspecific or closely related gibbon species. Conclusions and Relevance: This study showed no serious health problems that require immediate attention. However, relatively low alpha diversity and few potential bacteria related to gastrointestinal diseases and streptococcal infections were detected. Information on microbial composition is essential as a guideline to sustain a healthy gut condition of captive gibbons in NWRC, especially before releasing this primate back into the wild or semiwild environment. Further enhanced husbandry environments in the NWRC are expected through continuous health monitoring and increase diversity of the gut microbiota through diet diversification.